A ética lacaniana e o ato suícida - Soares, Josiane Borges (My University, 2024)
It is known that attempting against life occurs in society. Little, however, is mentioned about it; but this taboo does not prevent it from continuing to happen. Therefore, it is necessary to raise questions regarding psychoanalysis and ethics: how does ethics dialogue with psychoanalysis? What is the ethical-psychoanalytic perspective on suicide? In light of this, this research analyzes the relationship between the ethics of psychoanalysis regarding the suicidal act, and pointing out the implications of psychoanalysis in relation to the act of a person attempting suicide. The theoretical base originates mainly from Jacques Lacan and, for the dissertation on topics between ethics and psychoanalysis, there are the contributions from authors such as Aristotle, Hans Jonas, Immanuel Kant and Júlio Cabrera. This is a bibliographic study. A consideration worth mentioning is that psychoanalysis dialogues with ethics when it listens to the individuals without judging them and guiding them in finding a place for the anguish that affects them and that could make them attempt at taking their own lives and give up their status of desiring subject. [resumo fornecido pelo autor]
Sabe-se que atentar contra a vida é algo que ocorre na sociedade, porém, pouco se fala sobre isso. No entanto, esse tabu não impede que isso continue ocorrendo. Com isso, é preciso levantar alguns questionamentos quanto à psicanálise e à ética: como a ética dialoga com a psicanálise? Qual o olhar ético-psicanalítico perante o suicídio? Diante disso, esta pesquisa buscou analisar a relação da ética da psicanálise no que tange ao ato suicida, além de apontar quais as implicações da psicanálise no que se refere ao ato de um sujeito atentar contra a própria vida. O aporte teórico é construído, principalmente, por Jacques Lacan; e, para o assim como no delineamento dos tópicos entre a ética e a psicanálise, tem-se os apontamentos de autores como Aristóteles, Hans Jonas, Immanuel Kant e Júlio Cabrera. Trata-se de um estudo bibliográfico. Como considerações, tem-se que a psicanálise dialoga com a ética, quando escuta o sujeito, sem julgá-lo, mas guiando-o a dar um lugar para a angústia que o acomete e que pode fazer com que ele atente contra a própria vida e renuncie sua condição de sujeito desejante. [resumo fornecido pelo autor]
Keywords: Ética; Suicídio; Angústia; Psicanálise; Ethics; Suicide; Anguish; Psychoanalysis